Facile immobilization of DNA using an enzymatic his-tag mimic. Issue 97 (22nd November 2017) - Röthlisberger, Pascal; Levi-Acobas, Fabienne; Sarac, Ivo; Baron, Bruno; England, Patrick; Marlière, Philippe; Herdewijn, Piet; Hollenstein, Marcel
Abstract : Here, we present a generally applicable enzymatic method for the facile immobilization of single stranded DNA oligonucleotides on a solid support. Abstract : Methods for immobilization of DNA on solid supports are in high demand. Herein, we present a generally applicable enzymatic method for the immobilization of DNA without any prior chemical derivatization. This strategy relies on the homopolymerization of the modified triphosphate dImTP by the TdT. The resulting enzymatic his-tag mimic ensures binding of DNA on Ni-NTA agarose. The usefulness of this method is highlighted by the immobilization of functional nucleic acids without impairing their specific activities.